Broad-based subsidies or targeted transfers? Distributional equity vs macroeconomic costs. Issue 3 (3rd July 2022) - Feltenstein, Andrew; Datta, Biplab Kumar
ABSTRACT: We study the trade-off between "broad-based energy subsidy" and "subsidy reform and targeted transfer" in the developing country context. We analyze the incidence of an electricity tariff differential subsidy program in Pakistan and find that the greater share of subsidy benefit goes to relatively non-poor households. We then conduct a computable general equilibrium exercise of electricity subsidy reform and targeted transfer, and our results indicate that redistributing savings from electricity subsidy reform improves poor households' real income. However, this comes at the cost of short-term economic slowdown, before the economy returns to the benchmark level in the long term.